Dampak Pandemi Covid-19 terhadap Proses Pembelajaran di Taman Pendidikan Al-Qur’an (TPQ) - Nur Hasanah; Abd Mujahid Hamdan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
In 2020 the Covid-19 pandemic has become a global problem and has an impact on all aspects of life, including education. The learning process in all educational institutions, both formal and non-formal, was affected by the Covid-19 pandemic. One of the educational institutions affected by this pandemic is the Al-Qur'an Education Park (TPQ). The Covid-19 pandemic made the government try to suppress the spread of Covid-19, with that the government issued a policy to all educational institutions to close, then switched to Distance Learning (PJJ) and Learning From Home (BDR). Many of the educational institutions carry out an online learning process (online), but not all levels of society are able to adapt to the online learning process, especially those in rural areas. So this research aims to obtain information about the impact of the Covid-19 pandemic on the learning process at TPQ. This research uses a qualitative approach with a case study method. In this study, 5 respondents were selected, namely TPQ teachers in Kutelintang Village, Blangkejeren District, Gayo Lues Regency. The results of this study obtained information that the learning process at TPQ took place face-to-face, and generally the learning process at TPQ was less effective because there were too many holidays. So that it has an impact on students, teachers and parents. In addition, TPQ also played an important role in disseminating the Covid-19 pandemic to students.